Microscopic surface topography of a wrought superalloy processed by laser shock peening. (August 2016) - Lu, G.X.; Liu, J.D.; Qiao, H.C.; Zhang, G.L.; Cui, C.Y.; Zhou, Y.Z.; Jin, T.; Zhao, J.B.; Sun, X.F.; Hu, Z.Q.
Abstract: Surface topography of an upsetting wrought superalloy processed by laser shock peening was observed in microscale and a series of morphological characteristics such as surface reliefs with special orientation, destructive dimples were found. The longitudinal sizes of the micro surface structures are within 100 nm to 1000 nm generally. The mechanical response laws of metal materials under laser shock were proposed to explain the emergence of the special micro-structure characteristics. It can be concluded that the formation of surface reliefs is a release way of the internal stresses under laser shock and small dimples are deemed as an external representation of the release of impact energy in the mode of fracture damage. Highlights: Surface topography of a wrought superalloy processed by LSP was observed. Surface reliefs were found and a formation mechanism for them was proposed. Some microscale surface structures formed after LSP. The roughness profiles of the central regions in the shocked areas were analyzed.